Exascale MPI-based program deadlock detection - AlDhubhani, Raed (2015)
Deadlock detection is one of the main issues of software testing in High Performance Computing (HPC) and also in exascale computing areas in the near future. Developing and testing programs for machines which have millions of cores is not an easy task. HPC program consists of thousands (or millions) of parallel processes which need to communicate with each other in the runtime. Message Passing Interface (MPI) is a standard library which provides this communication capability and it is frequently used in the HPC. Exascale programs are expected to be developed using MPI standard library. For parallel programs, deadlock is one of the expected problems. In this paper, we discussed the deadlock detection for exascale MPI-based programs where the scalability and efficiency are critical issues. The proposed method is implemented to detect and flag the processes and communication commands which are potential to cause deadlocks in a scalable and efficient manner. MPI benchmark programs were used to test the propose method.